Incentives for Students: Evidence from Two Natural Experiments - Philipp Beltz; Susanne Link; Andreas Ostermaier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Incentives are widely used to increase peoples effort and thus performance. Whileacademic achievement depends heavily on effort, there is little empirical evidence onhow students respond to incentives other than grades and monetary rewards. We drawon two natural experiments that occurred at a major European university and use thedifference-in-differences approach to show how program and course policies affect theeffort and performance of students. Our findings indicate that students perform worse(i) if their effort is rewarded belatedly, (ii) if their effort has little impact on their finalgrade, or (iii) if they may resit exams more often and thus less effort is required from them.
Keywords: I21; I23; I28; 330; Performance; incentives; higher education; natural experiment; differencein- differences approach; Studierende; Ökonomischer Anreiz; Arbeitsleistung; Bildungsniveau; Feldforschung